Peran Guru KB-TKIT Mardhatillah Dalam Penerapan Pola Hidup Sehat dengan Gizi Seimbang - Hilmiah; Malik, Lina Revilla (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to understand the role of teachers in implementing healthy lifestyles with balanced nutrition at TKIT Mardhatillah. Teachers play a vital role in guiding children to understand the importance of balanced nutrition and personal hygiene as part of developing healthy habits from an early age. This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The results indicate that teachers at TKIT Mardhatillah actively promote healthy lifestyles through daily activities such as handwashing, consuming healthy food, and maintaining body hygiene. Moreover, teachers collaborate with parents to ensure that children practice healthy habits not only at school but also at home. The challenges faced in implementing these habits include children's inconsistent practices at home, which sometimes do not align with the lessons taught at school. Cooperation between teachers and parents is crucial to establish consistency in the implementation of healthy lifestyles and balanced nutrition for children. The findings of this study emphasize the critical role of teachers in educating young children about health and nutrition, and the need for family support to ensure the continuity of health programs implemented at school.